Neuromodulation accompanying focused ultrasound-induced blood-brain barrier opening - Chu, Po-Chun (Sci Rep, 2015)
Burst-mode focused ultrasound (FUS) induces microbubble cavitation in the vasculature and temporarily disrupts the blood-brain barrier (BBB) to enable therapeutic agent delivery. However, it remains unclear whether FUS-induced BBB opening is accompanied by neuromodulation. Here we characterized the functional effects of FUS-induced BBB opening by measuring changes in somatosensory evoked potentials (SSEPs) and blood-oxygen-level dependent (BOLD) responses. Rats underwent burst-mode FUS (mechanical index (MI) of 0.3, 0.55 or 0.8) to the forelimb region in the left primary somatosensory cortex to induce BBB opening. Longitudinal measurements were followed for up to 1 week to characterize the temporal dynamics of neuromodulation. We observed that 0.8-MI FUS profoundly suppressed SSEP amplitude and prolonged latency, and this effect lasted 7 days. 0.55-MI FUS resulted in minimal and short-term suppression of SSEP for less than 60 minutes and didn’t affect latency. BOLD responses were also suppressed in an MI-dependent manner, mirroring the effect on SSEPs. Furthermore, repetitive delivery of 0.55-MI FUS every 3 days elicited no accumulative effects on SSEPs or tissue integrity. This is the first evidence that FUS-induced BBB opening is accompanied by reversible changes in neuron responses, and may provide valuable insight toward the development of FUS-induced BBB opening for clinical applications.